Optimization of the fermentation culture conditions of Bacillus amyloliquefaciens ck-05 using response surface methodology - Liu, Xiaoyu; John Martin, Jerome Jeyakumar; Li, Xinyu; Zhou, Lixia; Li, Rui; Li, Qihong; Zhang, Jianwei; Fu, Dengqiang; Cao, Hongxing (Frontiers in Microbiology, 2025)
Bacillus amyloliquefaciens is widely recognized for its potential as a biofertilizer and biocontrol agent in agriculture due to its plant growth-promoting (PGP) mechanisms. However, the practical application of this bacterium is often limited by suboptimal fermentation conditions, which hinder its growth and efficacy. While numerous studies have optimized growth conditions for various strains of B. amyloliquefaciens, the novelty of this work lies in the systematic optimization of fermentation conditions for B. amyloliquefaciens ck-05, a strain obtained from a culture collection, and its potential application as a biofertilizer. In this study, single-factor experiments were conducted to evaluate the effects of carbon and nitrogen sources, inorganic salts, pH, temperature, culture time, rotation speed, inoculation rate, and liquid volume on the OD600 value of strain ck-05. A Plackett-Burman design was used to identify the significant factors influencing OD600, followed by a Box-Behnken design to determine the optimal growth conditions. The results revealed that soluble starch, peptone, and magnesium sulfate significantly impacted the growth of B. amyloliquefaciens ck-05. The optimized fermentation conditions were determined to be pH 6.6, temperature 30°C, culture time 40 h, rotation speed 150 rpm, inoculum rate 0.8%, and liquid volume 40%. Post-optimization, the OD600 of the fermentation broth increased by 72.79% compared to pre-optimization levels. The culture and fermentation conditions for B. amyloliquefaciens ck-05 were successfully optimized, providing a theoretical foundation for the future development of this strain as a microbial fertilizer.